Analisis Pengaruh Beban Pajak Kini, Beban Pajak Tangguhan, Dan Perencanaan Pajak Terhadap Manajemen Laba - Achsan, Muhammad Rauja; Nurhayati, Nurhayati (Universitas Pamulang, 2024)
This research aims to empirically determine the influence of current tax burden, deferred tax burden and tax planning on earnings management in automotive companies listed on the Indonesia Stock Exchange (BEI). during the 2018-2022 period. The research method used is a quantitative research method. The data used is secondary data, namely financial reports listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sample was selected using the purposive sampling method. Based on predetermined criteria, there were 6 automotive companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The analysis techniques used in this research are descriptive statistical analysis, panel data regression model testing, classical assumption testing, panel data linear regression testing, and hypothesis testing. The results of this research show that current tax burden and tax planning have an effect on earnings management, while deferred tax burden has no effect on earnings management. Then research simultaneously current tax burden, deferred tax burden, and tax planning influence on earnings management.